Relationships between Personality and Perceptions of Interactions - Smith, C. V. (Institutional Knowledge at Singapore Management University, 2007)
Although sexuality is an important component of personal relationships, there has been relatively little research on relationships between personality and everyday sexual behavior. Moreover, existing research on sexual behavior and personality (defined in terms of the Five-Factor Model, FFM) has found weak and inconsistent relationships. We hypothesized that sexual behavior can be better understood in terms of a model of personality that focuses on sexuality rather than in terms of a general model of personality. The present study examined relationships between two models of personality and daily sexual behavior. For 3 weeks, two different samples described their sexual interactions and they completed a measure of the FFM (N = 104) and the Sexy Seven (N = 48). A series of multilevel modeling analyses found that personality as measured by both models was related to both positive (e.g., feeling desired) and negative (e.g., feeling guilty) reactions to sexual experiences. As predicted, comparisons of the strength of the relationships between reactions to daily sexual experience and the two models found reactions to sexual experience were related more strongly to the Sexy Seven than to the FFM. The importance of considering both domainspecific and general measures of personality is discussed in terms of understanding sexual behavior.